3D computer-aided single stage correction of Crouzon related craniofacial and occlusal deformities: A case series of three adult patients - Hossam Hassan Fawzy; Hesham Abo Rahma; Moaz Elsheikh; Mohamed Abdalla Elnahas; Khaled Adel Eid; Yasser Elsheikh (Oral and Maxillofacial Surgery Cases, 2024)
Background: Single-stage surgical correction of Crouzon syndrome aims to remodel the cranial vault to achieve a morphology approaching age-matched norms. Virtual surgical planning (VSP) and computer-aided design (CAD) technology are recently used in craniofacial surgery. We aimed to determine the value of 3D planning tools and VSP in guiding different steps of surgical correction in craniofacial deformities in patients with untreated Crouzon syndrome. Methods: This study included three patients with delayed presentation of untreated Crouzon syndrome who underwent cranial vault remodeling preoperatively guided by VSP techniques between Jan 2021 and Feb 2023. Preoperative evaluation included all patients' physical examinations and 3D computed tomography (CT) scans. The constructed 3D files from the CT data were subsequently used for preoperative measurements. DICOM files of both preoperative and postoperative data were introduced into the medical 3D software. Results: The patients' ages at surgery were 18, 20, and 23 years. All patients had satisfactory aesthetic and functional outcomes with no major complications. The average operative time was 8.35 ± 2.53 hours. There was an improvement regarding cephalometric analysis and orbital morphology. The Presimulation movement distance regarding the frontal and zygomatic bone advancement showed a significant increment with a degree of overcorrection, significantly different from the preplanned. Conclusion: In conclusion, VSP is revolutionizing the surgical approach to complex craniofacial and occlusal malformations. This study successfully reports the use and applicability of VSP in untreated adult patients in a single stage. Combining the surgeon's experience and the appropriate use of computer-assisted surgery ultimately leads to successful surgery.